A green surfactant-assisted synthesis of hierarchical TS-1 zeolites with excellent catalytic properties for oxidative desulfurization. Issue 16 (1st February 2016) - Du, Shuting; Li, Fen; Sun, Qiming; Wang, Ning; Jia, Mingjun; Yu, Jihong
Abstract : Hierarchical TS-1 zeolites with intracrystalline mesopores are synthesized via a green surfactant-assisted route, showing excellent performance in oxidative desulfurization. Abstract : Hierarchical TS-1 zeolites with uniform intracrystalline mesopores have been successfully synthesized through the hydrothermal method by using the green and cheap surfactant Triton X-100 as the mesoporous template. The resultant materials exhibit remarkably enhanced catalytic activity in oxidative desulfurization reactions compared to the conventional TS-1 zeolite.